PEMAHAMAN NILAI-NILAI AJARAN AGAMA (ANALISIS PENDEKATAN TEORI KONFLIK DAN TEORI FUNGSIONAL) - Damanik, Nurliana (Studia Sosia Religia, 2024)
Religion has two main forces, namely as a factor of the power of unifying power (centripetal) and a factor of strength of divisive power (centrifugal). In a pluralist, multiethnic society, language and religion are presented as centripetal factors and also function as social control and motivators of development with a human dimension. Even religion also acts as an instrument of glue for the integrity of the nation. The critical function of religion is necessary not only to sensitize the mindset and behavior of individuals in society, but also to provide direction to development concepts and planning. Conflict theory arose as a reaction to the emergence of functional structural theory. Functional theory in sociology is one of the perspectives in sociology that views society as a system consisting of parts that are interrelated with one another. This theory views that society is static or in a balanced change, where each element of society has a role in maintaining stability. While conflict theory is a situation that everyone does not want because it harms material and nonmaterial. Marx and Weber categorically rejected the idea that society tends to lead to basic consensus or harmony, in which the ongoing structure of society works for the good of everyone. From these two things, it can be concluded that conflict is a social phenomenon that is present in social life, so conflict is inherent, meaning that conflict will always exist in every time and space, anywhere and anytime. In this view, society is an arena of conflict or an arena of conflict and integration that always takes place. Therefore, conflict and social integration are symptoms that always fill every social life, and the function and role of religion needs to be maintained in social and state life as the main force.